Protocol for exploring pathways to equitable outcomes in post-stroke aphasia and dysphagia. - Charles Ellis; Marcello Perraillon; Richard Lindrooth; Molly Jacobs; Karen Hegland; Anouk Grubaugh; Candice Adams-Mitchell (PLoS ONE, 2024)
Introduction Longstanding racial disparities in stroke-related outcomes have been well documented. However, the underlying causes of observed disparities have neither been clearly determined nor have strategies to mitigate disparities been developed. Evidence suggests that racial disparities may be partially explained by structural barriers that can arise from implicit and explicit provider biases, institutional practices, public policies, or characteristics of the community where patients reside and recover from their conditions. The objective of this study is to move beyond traditional measures of disparities by identifying the mechanisms that drive these observed disparities in aphasia and dysphagia across the continuum of care. In this study we will follow stroke survivors for 12 months post-discharge, which will allow us to examine the patient, provider, health system, and administrative factors that impact their aphasia and dysphagia recovery. Methods This study will utilize a 100% sample of Medicare fee-for-service claims data for persons hospitalized for stroke. Patients discharged from acute stroke care will be followed for at least 12 months to measure the timing of post-acute care transition(s) and post-acute care speech-language pathology (SLP) utilization. Functional communication and swallowing outcomes will be measured at initiation, conclusion of post-acute care treatment, and points in-between allowing us to link improvement of functional communication (i.e., aphasia) and swallowing ability (i.e., dysphagia) to aphasia/dysphagia treatments as patients transition through post-acute settings. Then, using regression decomposition methods, we will examine the relationships between race and: (a) where patients receive treatment, (b) the timing of transition between sites of care, and (c) the quality of care received. Decomposition methods will allow us to elucidate the multiple factors that contribute to underlying observed health disparities by quantifying the extent to which differences between the outcomes of two groups are explained by 1) differential endowments or characteristics, such as geographic access, education, risk factors, or insurance coverage; or 2) differences in decision-making, defined as between group differences in outcomes despite equal endowments or unmeasured differences. Discussion We hypothesize that racial disparities in aphasia and dysphagia outcomes will not only result from differences in the quantity and timing of services provided in the post-acute and community settings, but also structural differences at the community level. These findings will provide a more comprehensive understanding of healthcare use and outcomes.